(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate the impact of extensive and intensive production systems on the carcass traits and meat quality of northern Moroccan goat kids from Bouhachem Park, Morocco. Materials and Methods: Nine 6-month-old male goat kids were reared extensively on mountain pastures in the Chefchaouen region (Bouhachem Park) before slaughter. Body weights and linear measurements were recorded, and comprehensive analyses were conducted to evaluate the nutritional, technological, and sensory characteristics of their meat. The findings were then compared with data from nine intensively reared male goat kids. Results: Extensively reared goat kids demonstrated significantly superior growth performance and carcass characteristics (p < 0.05). Their meat exhibited lower fat content (2.24/100 gm vs. 5.23/100 gm) and reduced cholesterol levels (28.87 mg/gm vs. 40.07 mg/gm) compared to meat from intensively reared goat kids. Additionally, the fatty acid profile was more favorable, characterized by a lower proportion of saturated fatty acids (45.77% vs. 47.48%), a higher polyunsaturated fatty acid content (16.85% vs. 8.72%), and an increased percentage of desirable fatty acids (72.84% vs. 70.52%). The semimembranosus muscle from extensively reared kids had significantly lower pH values (5.88 vs. 6.00). However, both outdoor- and indoor-raised kids showed acceptable meat color redness and shear force values. Sensory panel evaluations indicated a clear preference for extensively reared goat meat in terms of color, flavor, herbaceous aroma, and overall acceptability. Conclusion: Goat kids from Bouhachem Park pastures demonstrated promising results in growth performance, carcass traits, and meat quality. Their meat represents a valuable dietary option, offering high nutritional value and a superior sensory profile. J. Adv. Vet. Anim. Res., 12(3): 728–739, September 2025 http://doi.org/10.5455/javar.2025.l936